Dampak Pelanggaran ASN Atas SE Menteri PANRB N0. B/2355/M.PANRB/07/2015 Dalam Layanan Birokrasi - Syaefullah Syaefullah (Jatiswara, 2019)
The side of the government bureaucracy to the political power or the dominant group makes the bureaucracy not sterile. Many viruses continue to irritate it like; impartial service, far from objectivity, too bureaucratic, etc., as a result they feel stronger themselves, immune from supervision. The descriptions above may be concluded that the neutrality of the bureaucracy will always be associated with political elements and political power; in this case the political element is defined as the power to make decisions, while the political power is all political aggression in the form of political parties. With the issuance of Law Number 5 of 2014 concerning ASN, in which the law has been regulated and determined in the form of restrictions and sanctions that will be received by a member of the ASN Public Servants and Government Employees with this Work Agreement (PPPK). By looking at the phenomena or opinions above, the writer tries to give a little review of the various impacts that will occur on the roles and functions of civil servants ASN and PPPK if they are not neutral in bureaucratic services as follows: 1. Community interests are distorted, 2 Services are not optimal, 3. Position placement tends to see the involvement in the election, 4. The position of the bureaucracy is filled by incompetent civil servants. That in order to maintain the neutrality of ASN in the election, it is very necessary: There is a strengthening of the ASN Code of Ethics with clear and firm limitations, There is a guarantee of protection in maintaining the neutrality of ASN; Collaboration with BKN is established to provide administrative sanctions in the form of not being promoted to ASN, Construction of KASN cooperation, Regional Civil Service Agency (BKN) with Regional Civil Service Agency (BKD) as a source of information in the regions, and Bawaslu to oversee the election and election throughout the Republic of Indonesia. Access to reporting or advocacy on issues of centralization in all parts of Indonesia, as well as guarantees for reporters;